Analisis Kualitas Pelayanan Jasa Pada Salon dan Spa Muslimah Baiti Ummi Disungai Jawi Kota Pontianak - aisyah; Erlisa Yulianti (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2021)
study discusses the quality or service by using five dimensions, namely Tangibles, Reliability, Responsiveness, Assurance, and Empathy at the Salon and Spa Muslimah Baiti Ummi. The research method used is the descriptive quantitative method while the population and sample used are costumers or consumers in the Salon and Spa Muslimah Baiti Ummi and the distribution of questionnaires as many as 76 respondents. Collecting data using the method of observation, interviews and questionnaires. The data analysis used was the mean test, Tki analysis, validity test, and reliability test. Based on the results of research on the Salon and Spa Muslimah Baiti Ummi it is said to be good. This can be seen from the results of the analysis with the amount of data as many as 76 respondents which can be seen from the average level of importance that is 4.04 and while the average value og the performance level is 4.02. So the level of conformity between the level of performance og the Salon and Spa Muslimah Baiti Ummi with the level of importance hat not fully achieved customer expectations because the conformity level is less than 100%. Key Words: Quality of Service (Tangible, Reliability, Responsivensess, Assurance, and Empathy)